Implementation of Time Stamp as a Form of Legal Certainty Regarding the Cyber Notary Concept - Tandiono, Sudargo; Rahmasari, Nuzul Shinta Nur; Berliana, Rizka Aprilia; Adjie, Habib (Sultan Agung Notary Law Review, 2024)
As time progresses, of course, existing technology also develops. Entering the 4.0 era which begins to require the implementation of digitalization from various sectors. In addition to making it easier, the digitalization era can minimize errors that occur due to human error. In this case, special challenges are encountered in the implementation of Cyber Notary. Explanation of Article 15 Paragraph (3) of the Notary Law only mentions the authority to certify a transaction carried out electronically (Cyber Notary). However, unfortunately, regarding the authority of the Notary in terms of Cyber Notary, there are no further regulations. This study uses a normative legal research method with a conceptual approach and focuses on the use of time stamps in the duties of a notary related to the duties and authorities of a notary, namely making authentic deeds. The time setting on the time stamp provides a sign that the authentic document or deed was made in a unit of time that can be accounted for by using the services of a third party, namely the time stamp authority. The existence of a third party is needed because the time on each computer can vary. Therefore, a third party is needed who can guarantee this. In this case, the Ministry of Law and Human Rights can be trusted to overcome this problem.